Uma plataforma para avaliar a experiência dos usuários com aplicativos para smartphones - Kronbauer, Artur H.; Machado, Díferson; Santos, Celso A. S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2014)
In recent years, after the great proliferation of mobile devices, the relationship between usability, context and emotions of the users is a widely discussed in studies related to user experience (UX) theme. Evaluations show that humans typically interact with computer systems in unusual ways and have different feelings about the applications. To contribute to this area of study, this paper presents a platform for the collection and analysis of data related to the user experience of mobile data. To evaluate the potential of the platform, an experiment was conducted with the participation of 68 people, for thirty days. The study results are presented and discussed throughout the paper.